Comprehensive Analysis of MYB Gene Family and Their Expressions Under Abiotic Stresses and Hormone Treatments in Tamarix hispida - Zhang, Tengqian; Zhao, Yulin; Wang, Yucheng; Liu, Zhongyuan; Gao, Caiqiu (Frontiers in Plant Science, 2018)
The MYB transcription factors (TFs) is a plant TF families, which involves in hormone signal transduction, and abiotic stress tolerance, etc. However, there are few studies on the MYB TFs family and its regulatory mechanism in Tamarix hispida. In this study, 14 MYB genes (named ThMYB1 - ThMYB14) were cloned and characterized from T. hispida. The transcription profiles of ThMYBs in T. hispida under different abiotic stress conditions were monitored using qRT-PCR. Most of studied ThMYBs were significantly downregulated and/or upregulated by salt and osmotic stress, ABA, GA3 and JA treatments in at least one organ. Especially, ThMYB13 was induced in the leaves and roots of T. hispida when exposed to NaCl treatment at all study periods, indicating that it may involve in salt stress. To further study ThMYB13 function, ThMYB13 overexpression and knock-down plants and control plants transformed with an empty pROKII were obtained using a transient transformation system. Overexpression of ThMYB13 in T. hispida displayed the lowest O2-, H2O2 and MDA accumulation, minimal cell death, the most stable K+/Na+ ratio and the lowest electrolyte leakage rate among the three kinds of transient expression in T. hispida. Conversely, the RNAi-silencing, transiently transformed plants displayed the opposite physiological changes. Therefore, ThMYB13 might play a role in salt stress tolerance in transgenic T. hispida plants.